1992
DOI: 10.1093/jnci/84.10.785
|View full text |Cite
|
Sign up to set email alerts
|

Direct Photoaffinity Labeling of Tubulin With Taxol

Abstract: This observation is the first step in a study to determine the binding site for taxol on the microtubule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(73 citation statements)
references
References 0 publications
0
72
0
1
Order By: Relevance
“…tide-We decided to explore the potential of the direct photoaffinity labeling technique for providing information about the dolastatin 10-binding site on tubulin based on the successful studies with colchicine (17), paclitaxel (40), and GTP (9). Only in the latter case was a specific amino acid residue, Cys-12 of ␤-tubulin, identified, and Shivanna et al (9) proposed that exposure of tubulin to ultraviolet radiation resulted in generation of sulfhydryl free radicals as the reactive species.…”
Section: Direct Photoaffinity Labeling Of Tubulin By [ 3 H]dolastatinmentioning
confidence: 99%
“…tide-We decided to explore the potential of the direct photoaffinity labeling technique for providing information about the dolastatin 10-binding site on tubulin based on the successful studies with colchicine (17), paclitaxel (40), and GTP (9). Only in the latter case was a specific amino acid residue, Cys-12 of ␤-tubulin, identified, and Shivanna et al (9) proposed that exposure of tubulin to ultraviolet radiation resulted in generation of sulfhydryl free radicals as the reactive species.…”
Section: Direct Photoaffinity Labeling Of Tubulin By [ 3 H]dolastatinmentioning
confidence: 99%
“…Assembly was monitored spectrophotometrically at 350 nm by following the change in turbidity that is representative of polymer mass (16). Electron microscopy was performed as described previously (3). Photoaffinity Labeling Studies and CNBr Digestion-For mapping studies, 1 mM GTP was added to 1 mg/ml MTP in assembly buffer at 37°C.…”
Section: Preparation and Polymerization Of Microtubule Protein (Mtp)-twomentioning
confidence: 99%
“…First, we have shown that direct photolabeling of tubulin with Taxol resulted in the labeling of ␤-tubulin (3). Further studies with [ 3 H]3Ј-(p-azidobenzamido)Taxol (where the arylazide was incorporated into the C-13 side chain) resulted in the isolation of a photolabeled peptide containing amino acid residues 1-31 in ␤-tubulin (10).…”
mentioning
confidence: 99%
“…It has also shown some activity against various other tumour types (Etlinger, 1993;Forastiere, 1993;Einzig and Wiernik, 1995;Edelman and Gandara, 1996). Although the mechanism by which stable microtubules are induced by taxol are well established (Schiff et al, 1979;Rao et al, 1992Rao et al, , 1994, the molecular links between tubulin polymerisation, cell-cycle arrest, and ultimately cell death are not so well characterised. Given the broad spectrum of activity of taxol with regard to tumour type and genetic background, it is important that these mechanisms are resolved.…”
mentioning
confidence: 99%